Da agroindústria canavieira ao setor sucroenergético em Goiás: a questão técnico-gerencial e as estratégias de controle fundiário - Silva, William Ferreira da (2016)
The sugar cane crop, one of the oldest economical activities of the country, has already crossed different economical, technological, cultural and social periods occurred in Brazil, resulting in expansion and retraction movements. Driven by the market conditions and governmental programs this secular activity has passed recently, through one more expansion cycle, this time reaching, in a decisive way, the Cerrado goiano spaces. The occupation movement of these new spaces was encouraged by the entering of foreign investors’ capital and accompanied by a movement of the modernization of techniques and management. The expansion has showed sufficient strength to change the territorial and spatial dynamic construction, with emphasis to the control of the necessary production resources. The present study has as the objective to analyze the strategies used by the sugar cane money, in the current expansion phase, to establish the control over the land and its consequences about the land property. Despite of the changes related to the capital origin and composition, the verticalized productive structure is maintained as one of the strongest characteristics of this activity, condition which requires the control over the territory where the agricultural production is realized. From the data and information collecting on by the representatives of the sugar cane capital, land owners, Rural Unions and rural realtors it was tried to evaluate the sugarcane agro industry action over the land property in two expansion areas in Goiás state, located in the Southwest and in the middle North of the state. The data analysis and the reflection about the theme indicate that the sugarcane agro industry is suiting itself to the principles of the flexible accumulation regimen without waiving of the productive structure verticalization. The central interest in the territory domination strategy is the maintenance of the capacity to improve the land profit and to guarantee the supplying of the agribusiness unities. Therefore, the land control occurs by leasing/agricultural partnerships against the land ownership and the recruitment of suppliers.